PEREMPUAN DALAM POLITIK (STUDI KASUS PARTISIPASI SELEBRITIS PEREMPUAN DALAM KOMUNIKASI POLITIK DI PARTAI-PARTAI ISLAM PADA PEMILU 2014 DI INDONESIA) - Mohammad Zamroni (Profetik: Jurnal Komunikasi, 2015)
This study was conducted to see the participation of celebrity women, especially Okky Asokawati board of PPP and Dessy Ratnasari board of PAN in political communication in political parties and in the legislature that will be studied on the issue of celebrity women as a political communicator, the delivery of those messages, media political communication used, audiences politics becomes the target, and analysis of the effects of political communication appears. This research is a single case study with a phenomenological approach and includes descriptive analytical research.The results showed: First, the level of welfare of the female celebrities really should not be feared, even those above the average rate of other women's welfare. Second, not all access to economic resources, social and political for women available in both formal and informal institutions, including the Third, female celebrities today are more aware and critical of the various forms of life, especially for urban communities with more advanced levels of education. Fourth, the role of women in the legislature and political parties are not yet on par with the participation of men. Fifth, in particular female celebrities do not have equality in terms of control / power the same as with men, to change the conditions of the position, the future of themselves and the community.